Effects of cigarette smoking on semen quality, reproductive hormone levels, metabolic profile, zinc and sperm DNA fragmentation in men: results from a population-based study - Osadchuk, Ludmila; Kleshchev, Maxim; Osadchuk, Alexander (Frontiers in Endocrinology, 2023)
Background: Cigarette smoking seems to have a negative impact on men's reproductive health, but our knowledge of its effects on the reproductive function of Russian men is still very limited. The purpose of this study was to evaluate the effect of cigarette smoking on semen quality, including sperm DNA fragmentation, hormonal, zinc and metabolic status in young men from the general multi-ethnic Russian population (n=1,222, median age 23 years) and to find out the ethno-specific effects of smoking by comparing male groups of different ethnicity.Methods: Each participant filled out a standardized questionnaire, provided one blood and semen sample.Semen parameters, serum reproductive hormones, lipids, glucose, uric acid and seminal zinc were analyzed.Participants were classified as smokers (n=450) and non-smokers (n=772), and smokers were stratified into moderate (≤10 cigarettes/day) and heavy (>10 cigarettes/day) smokers.Results: In the entire study population, heavy smokers were characterized by a decrease in semen volume, total sperm count, sperm concentration and motility, and an increase in sperm DNA fragmentation and teratozoospermia compared with non-smokers (p<0.05). There was also a reduction in the serum and seminal zinc level as well as an impairment in metabolic health in smokers compared with non-smokers (p<0.05). No significant differences between smokers and non-smokers were found for serum levels of LH, FSH, inhibin B, testosterone and estradiol. In the second part of our study, the most numerous ethnic groups of Slavs (n=654), Buryats (n=191), and Yakuts (n=125) were selected from the entire study population. Among three ethnic groups, the smoking intensity was higher in Slavs than in Buryats or Yakuts suggesting a greater tobacco addiction in Slavs than in Asians. A decrease in semen parameters and seminal zinc levels, and an increase in sperm DNA fragmentation and teratozoospermia was observed only in smoking Slavs (p<0.05); moderate decrease in testosterone and increase in triglyceride levels were revealed in smoking Yakuts (p<0.05), but no significant changes were detected in smoking Buryats.We concluded that cigarette smoking has an ethno-specific effect on male reproductive function, probably due to the different activity of the seminal antioxidant system, which is yet to be elucidated.